2010
DOI: 10.1016/j.resp.2010.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Congenital central hypoventilation syndrome and the PHOX2B gene: A model of respiratory and autonomic dysregulation

Abstract: The paired-like homeobox 2B gene (PHOX2B) is the disease-defining gene for congenital central hypoventilation syndrome (CCHS). Individuals with CCHS typically present in the newborn period with alveolar hypoventilation during sleep and often during wakefulness, altered respiratory control including reduced or absent ventilatory responses to hypercarbia and hypoxemia, and autonomic nervous system (ANS) dysregulation; however, a subset of individuals present well into adulthood. Thermoregulation is altered and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 123 publications
(174 reference statements)
1
40
0
1
Order By: Relevance
“…The evidence for both sympathetic and parasympathetic dysregulation in CCHS follows logically from a basic understanding of the PHOX2B gene role in embryologic development of the sympathetic, parasympathetic, and enteric pathways of the ANS (5,22). We postulate that the demonstrated functional differences in pupillary measures are specific to the ANS efferent pathways.…”
Section: Pupillometry In Cchsmentioning
confidence: 93%
See 1 more Smart Citation
“…The evidence for both sympathetic and parasympathetic dysregulation in CCHS follows logically from a basic understanding of the PHOX2B gene role in embryologic development of the sympathetic, parasympathetic, and enteric pathways of the ANS (5,22). We postulate that the demonstrated functional differences in pupillary measures are specific to the ANS efferent pathways.…”
Section: Pupillometry In Cchsmentioning
confidence: 93%
“…This is based on the absence of afferent defects as observed from a review of the records and demonstration that refractive variance (as demonstrated by the need or a lack of it for glasses) was not associated with differences in pupil measurements. PHOX2B expression patterns in mouse knockout models indicate a lack of PHOX2B expression at the level of the midbrain (Edinger-Westphal nucleus, pretectal nucleus) and hypothalamus (22). Consequently, we propose that pupillometry measures obtained in genetically confirmed CCHS can be used to elucidate efferent ophthalmologic ANS dysfunction and may have applicability in the evaluation of efferent pathways of other autonomic disorders.…”
Section: Pupillometry In Cchsmentioning
confidence: 99%
“…In addition, pathological evidence obtained from polyalanine repeat mutation (PARM) CCHS animal models supports the notion that central respiratory chemosensitivity relies on relatively few specialized neurons, such as the chemoreceptor neurons of the RTN (Dubreuil et al 2008;Ramanantsoa et al 2011). In this genetic disease, central chemosensitivity is essentially absent; severe hypoventilation occurs during sleep but relatively adequate breathing persists during waking, and some degree of exercise-induced hyperventilation remains, at least in the milder cases (Amiel et al 2003(Amiel et al , 2009Carroll et al 2010;Gozal, 1998;Shea et al 1993). The severity of the symptoms increases according to the number of extra alanine residues in the mutated polyalanine track of PHOX2B (Carroll et al 2010).…”
mentioning
confidence: 93%
“…In this genetic disease, central chemosensitivity is essentially absent; severe hypoventilation occurs during sleep but relatively adequate breathing persists during waking, and some degree of exercise-induced hyperventilation remains, at least in the milder cases (Amiel et al 2003(Amiel et al , 2009Carroll et al 2010;Gozal, 1998;Shea et al 1993). The severity of the symptoms increases according to the number of extra alanine residues in the mutated polyalanine track of PHOX2B (Carroll et al 2010). The respiratory symptoms of the disease suggest that the central respiratory controller located in the pre-Bötz-inger complex of CCHS patients is largely intact but that the brain of these individuals lacks neurons that are either uniquely specialized in detecting CO 2 or are specialized in funneling the excitatory influence of CO 2 to the respiratory controller.…”
mentioning
confidence: 99%
See 1 more Smart Citation